Assessment of emergency medicine residents: a systematic review - Colmers-Gray, Isabelle N; Walsh, Kieran; Chan, Teresa M (Canadian Medical Education Journal, 2017)
Background: Competency-based medical education is becoming the new standard for residency programs, including Emergency Medicine (EM). To inform programmatic restructuring, guide resources and identify gaps in publication, we reviewed the published literature on types and frequency of resident assessment. Methods: We searched MEDLINE, EMBASE, PsycInfo and ERIC from Jan 2005 - June 2014. MeSH terms included “assessment,” “residency,” and “emergency medicine.” We included studies on EM residents reporting either of two primary outcomes: 1) assessment type and 2) assessment frequency per resident. Two reviewers screened abstracts, reviewed full text studies, and abstracted data. Reporting of assessment-related costs was a secondary outcome. Results: The search returned 879 articles; 137 articles were full-text reviewed; 73 met inclusion criteria. Half of the studies (54.8%) were pilot projects and one-quarter (26.0%) described fully implemented assessment tools/programs. Assessment tools (n=111) comprised 12 categories, most commonly: simulation-based assessments (28.8%), written exams (28.8%), and direct observation (26.0%). Median assessment frequency (n=39 studies) was twice per month/rotation (range: daily to once in residency). No studies thoroughly reported costs. Conclusion: EM resident assessment commonly uses simulation or direct observation, done once-per-rotation. Implemented assessment systems and assessment-associated costs are poorly reported. Moving forward, routine publication will facilitate transitioning to competency-based medical education.